2020
DOI: 10.29138/prd.v2i2.234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Direct and Indirect Compensation on Performance of Employees PT. Terminal Petikemas Surabaya

Abstract: The purpose of this study is to analyze the effect of direct and indirect compensation on employee performance simultaneously and partially. The population in this study was 92 employees. This study uses a quantitative approach. The object of this research is direct compensation and indirect compensation at PT. Surabaya Container Terminal. The data collection methods used were questionnaires and interviews. The data analysis technique used is multiple linear regression. The results of the study are that direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The indirect compensation variable had Ni Putu Sinthia Damayanthi, Ni Made Suastini a moderate contribution of 41.2% to employee performance, according to the coefficient of determination test, and the remaining 58.8% was influenced by other variables not employed in this study. The findings of this study are consistent with those of previous research Ahmed (2014), Sri et al, (2020), andBrasilio andTridayanti (2020) which stated that indirect compensation has a significant effect on employee performance. In indicated that when indirect compensation increases, employee performance also increases.…”
Section: Others Benefitsupporting
confidence: 93%
“…The indirect compensation variable had Ni Putu Sinthia Damayanthi, Ni Made Suastini a moderate contribution of 41.2% to employee performance, according to the coefficient of determination test, and the remaining 58.8% was influenced by other variables not employed in this study. The findings of this study are consistent with those of previous research Ahmed (2014), Sri et al, (2020), andBrasilio andTridayanti (2020) which stated that indirect compensation has a significant effect on employee performance. In indicated that when indirect compensation increases, employee performance also increases.…”
Section: Others Benefitsupporting
confidence: 93%